Use of Bioactives from Carica papaya Seeds in Formulation and Evaluation of Solid Lipid Nanoparticles - Rima, R. Patil (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Papaya seeds are a rich source of proteins, fat, fibers, vitamins, minerals, monounsaturated fatty acids, polyphenols, and powerful antioxidants like flavonoids. Carica papaya is used for treating skin, fungal, viral, digestive, and dental disorders, as well as cancer, kidney, and nervous disorders. The bioavailability of a drug can be improved with the use of solid lipid nanoparticles (SLNs) if it is not very water-soluble. The targeted and controlled release of medications is another possible application. The objective of this research is to create and assess bioactive SLNs derived from C. papaya seeds. Materials and Methods: The ripe, shade-dried papaya seeds were first powdered and extracted using the Soxhlet method to obtain crude extract. Glycosides, alkaloids, tannins, saponins, phenols, and flavonoids were all assessed during the phytochemical examination. The SLNs of extract were formulated by a solvent evaporation method using Stearic acid as lipid and poloxamer 188 as surfactant. Several of characteristics were used to assess the prepared SLNs, including encapsulation efficiency, in vitro dissolution studies, zeta potential, particle size, and transmission electron microscopy (TEM). Chemical confirmation of the produced SLNs was achieved using Fourier transform infra-red (FT-IR) and powder X-ray diffractometry (XRD) analyses. The thermal stability of SLNs was studied with the help of differential scanning calorimetry (DSC). Results and Discussion: The improved formulation had a zeta potential of −28.4 mV and a polydispersity index of 0.021, and its particle size was determined to be 124.1 ± 22.3 nm. The effectiveness of drug encapsulation was determined to be 80.98 ± 1.59. Formation of SLN confirmed by TEM, FT-IR analysis, powder XRD, and DSC showed no unwanted peaks. The thermal stability of SLN was analyzed with the help of DSC. An in vitro drug release study showed 89.30 ± 0.55% release of the drug in 12 h. Conclusion: The evaluation results indicate an effective SLN formulation that might be used for antidiabetic effect.